2023
DOI: 10.1186/s10194-023-01604-2
|View full text |Cite
|
Sign up to set email alerts
|

The Registry for Migraine (REFORM) study: methodology, demographics, and baseline clinical characteristics

Abstract: Background Erenumab has demonstrated effectiveness for prevention of migraine attacks, but the treatment is costly, and a considerable proportion of patients do not respond to it. The Registry for Migraine study (REFORM) was initiated to discover biomarkers that can predict response to erenumab in patients with migraine. The specific objective was to investigate differences in erenumab efficacy based on clinical information, blood-based biomarkers, structural and functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…To our knowledge, this is the first meta-analysis to assess the association between AD and headache disorder. The fairly frequent coexistence of migraine and allergic diseases was well described in previous epidemiologic studies ( 30 , 31 ). While recent meta-analyses ( 11 13 ) have indicated a bidirectional association between asthma and headache disorder, our study extends this understanding.…”
Section: Discussionsupporting
confidence: 66%
“…To our knowledge, this is the first meta-analysis to assess the association between AD and headache disorder. The fairly frequent coexistence of migraine and allergic diseases was well described in previous epidemiologic studies ( 30 , 31 ). While recent meta-analyses ( 11 13 ) have indicated a bidirectional association between asthma and headache disorder, our study extends this understanding.…”
Section: Discussionsupporting
confidence: 66%
“…The present investigation is part of the larger parental Registry for Migraine (REFORM) study and was carried out at a single tertiary care unit [ 11 ]. The study protocol received approval from the relevant ethics committee and data protection agency.…”
Section: Methodsmentioning
confidence: 99%
“…All participants provided written informed consent before any study-related tasks or procedures were performed. A detailed description of the methods used in the parental study can be found elsewhere [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…REFORM is a prospective, single-center study that included participants from a single-arm, open-label, phase IV trial (NCT04265755) at the Danish Headache Center (5). The detailed methodology of REFORM is reported elsewhere (14).…”
Section: Overviewmentioning
confidence: 99%
“…Three PROMs were used as secondary measures: Migraine Disability Assessment (MIDAS) (21), Headache Impact Test (HIT-6) (22) and a shortened version of the World Health Organization Disability Assessment 2.0 (WHODAS 2.0) (23). MIDAS scores (the sum of missed days per three months because of headache) were categorized as "little or no disability" (0-5), "mild disability" (6-10), "moderate disability" (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or "severe disability" (!21) (21). HIT-6 scores in the range 36-78 were categorized as "little or no impact" ( 49), "some impact" (50-59), "substantial impact" (56-59) or "severe impact" (60-78) (22).…”
Section: Outcomes and Measuresmentioning
confidence: 99%